1995
DOI: 10.1042/bj3120693
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of cyclin A, cyclin B and p21 concentrations in a growth-restricted human fibroblast cell line

Abstract: When the culture temperature was shifted from 35 degrees C to 39 degrees C, human fibroblasts immortalized by the temperature-sensitive simian virus 40 T antigen became larger and acquired the morphological characteristics of senescent fibroblasts. After culture at 39 degrees C for 48 h, most cells had ceased to proliferate. A rapid depletion of cells with S-phase DNA content was observed after the temperature shift. To elucidate the mechanism governing this rapid arrest of proliferation, we studied the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Upon induction of p21, Tet-p21-1 and other Tet-p21 cells became larger, suggesting that they continued to grow in the absence of DNA replication, a phenomenon that is also observed in ®broblast senescence (Cristofalo et al, 1989). Consistent with this, a tenfold increase of p21 RNA has been observed as human ®broblasts become senescent (Noda et al, 1994), and increases in p21 RNA and protein are also found when human ®broblasts immortalized by the temperature-sensitive simian virus 40 T antigen are shifted to nonpermissive temperature, resulting in morphological characteristics of senescent ®broblasts (Tsao et al, 1995 other p53-dependent genes are also induced in irradiated cells, it is likely that p21 is responsible for cell cycle arrest. Consistent with this idea, it has been reported that the induced level of p21 in U.V.-irradiated cells is su cient to account for the observed inhibition Cdk2 activity, and may in part account for the decrease in Cdk4 activity (Poon et al, 1996).…”
Section: Discussionsupporting
confidence: 61%
“…Upon induction of p21, Tet-p21-1 and other Tet-p21 cells became larger, suggesting that they continued to grow in the absence of DNA replication, a phenomenon that is also observed in ®broblast senescence (Cristofalo et al, 1989). Consistent with this, a tenfold increase of p21 RNA has been observed as human ®broblasts become senescent (Noda et al, 1994), and increases in p21 RNA and protein are also found when human ®broblasts immortalized by the temperature-sensitive simian virus 40 T antigen are shifted to nonpermissive temperature, resulting in morphological characteristics of senescent ®broblasts (Tsao et al, 1995 other p53-dependent genes are also induced in irradiated cells, it is likely that p21 is responsible for cell cycle arrest. Consistent with this idea, it has been reported that the induced level of p21 in U.V.-irradiated cells is su cient to account for the observed inhibition Cdk2 activity, and may in part account for the decrease in Cdk4 activity (Poon et al, 1996).…”
Section: Discussionsupporting
confidence: 61%
“…There are three oncogenes, E5, E6, and E7, encoded by HPV (14,15,32). HPV-16 E6 and E7 can immortalize and transform primary cells, whereas E5 can transform established cells (28). The mechanisms of immortalization by HPV-16 E6 and E7 involve E6-mediated degradation of p53 and E7-mediated inactivation of the pRb protein (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to positive regulation by cyclins, CDK activity is also downregulated by association with inhibitory proteins, such as p21 WafI/SdiI/CipI , p53, p16, p15, and p27 (for a review, see ref- erence 24). The protein p21 is encoded by a recently cloned gene (Sdi) which is overexpressed in senescent fibroblast (21,28). Another group also showed that the same p21 protein encoded by the CipI gene can associate with different CDKcyclin complexes and inhibit the kinase activity that is required for cell cycle progression (13,30,31).…”
mentioning
confidence: 99%
“…The protein p21 (Waf1/SdiI/CipI) (p21) is encoded by a recently cloned gene (Sdi), which is overexpressed in senescent fibroblasts (22,28). The same p21 protein was found to associate with different cyclin-dependent kinase-cyclin complexes and to inhibit the kinase activity that is required for cell cycle progression (30,31).…”
mentioning
confidence: 99%